Impact of credit constraints on the development quality of new agricultural business entities: evidence from Jiangsu Province, China - Cheng, Lingjuan; Han, Pengju; Zou, Wei (Frontiers in Sustainable Food Systems, 2025)
Enhancing the development quality of new agricultural business entities is crucial for advancing agricultural modernization and achieving rural revitalization, while alleviating credit constraints is a key pathway toward this goal. Using survey data collected in 2021 from 427 grain-oriented new agricultural business entities in Jiangsu Province, this study employs an accelerated genetic algorithm–based projection pursuit model to measure their development quality and conducts empirical tests to examine the impact of credit constraints and their underlying mechanisms. The results show that: (1) the development quality of new agricultural business entities in Jiangsu still has considerable room for improvement and varies substantially across types, ranking from highest to lowest as agricultural enterprises, cooperatives, family farms, and large-scale farmers. Across benefit dimensions, economic benefits exceed social benefits, which in turn surpass ecological benefits; notably, cooperatives display slightly lower economic benefits than family farms, but their social benefits are second only to agricultural enterprises and far higher than family farms; (2) credit constraints exert significant negative effects on overall development quality as well as on each benefit dimension; and (3) credit constraints indirectly restrict development quality through two key transmission channels—fixed asset investment and the scale of transferred-in farmland. By uncovering these multidimensional mechanisms, this study provides robust empirical evidence on how credit constraints affect the development quality of new agricultural business entities, and offers valuable implications for alleviating credit constraints, improving rural financial supply, and promoting the high-quality development of agricultural business entities.